Improving Students’ Achievement on Writing Procedure Text by Using Group Investigation Strategy at SMK Sandhy Putra Medan - Resperdiana Purba; Lisna Evayanti Butar-butar (Politeknik Adiguna Maritim Indonesia, 2020)
The objective of this study was to find out if there was significant effect of applying Group Investigation Strategy on studentsâ€™ Achievement in Writing Procedure text. The population of this study was the second year students of SMK Sandhy Putra Medan, which consisted of seven parallel classes. Two classes were as the sample of the research. Every class consisted of 35 students. Therefore, there were 70 students became the sample of the study. The total number of students was divided into two groups, namely 35 students for experimental groups and another 35 students for control group. The experimental group was taught by Group Investigation Strategy, while control group was taught by using Explanation. The instruments of collecting data used the writing test. To obtain the reliability of the test, the researcher used Spearman Brown formula. The pre-test and post-test were administrated and then the data were analyzed by using the t-test formula. The result showed that the t-test was (3.57) is higher than t-table value (2.04) at the level of significance (0.05) for ð›¼ - two tail test (3.57>2.04), and the degree of freedom (df) was 68 Based on the analysis of the study, the result indicated that the he was accepted. It means that there is significant effect of applying Group Investigation Strategy on Studentsâ€™ Achievement in Writing Procedure Text